An Investment Framework for Nutrition in Zambia : Reducing Stunting and Other Forms of Child Malnutrition - Dayton Eberwein, Julia; Kakietek, Jakub; Shekar, Meera; Subandoro, Ali; Pereira, Audrey; Hyder, Zia; Sunkutu, Rosemary; Akuoku, Jonathan Kweku (World Bank, Washington, DC, 2017)
This paper builds on global experience and Zambia's specific context to identify aneffective nutrition approach along with costs and benefits of key nutrition interventions. It isintended to help guide the selection of the most cost-effective interventions as well as strategiesfor scaling these up. The paper considers both relevant "nutrition-specific" interventions, largelydelivered through the health sector, and multisectoral "nutrition-sensitive" interventions, delivered through other sectors such as agriculture, education, and water and sanitation. We estimate that the costs and benefits of implementing 10 nutrition-specific interventions would require an annual public investment of $40.5 million and would avert over 112,000 DALYs, save over 2,800 lives, and prevent 62,000 cases of stunting. Economic productivity could potentially increase by $915 million annually over the productive lives of the beneficiaries, with an impressive internal rate of return of 32 percent. However, because it is unlikely that the Government of the Zambia or its partners will find the $40.5 million necessary each year to reach full coverage, we also consider scale-up scenarios based on considerations of their potential for impact, burden of stunting, resource requirements, and implementation capacity. The two scenarios that scale up the nine most cost-effective nutrition-specific interventions (excluding the public provision of complementary foods) are the most advantageous in terms of cost-effectiveness and resource requirements and would require $11 million to scale up to partial levels and $23 to scale up to full coverage levels. Among the 8 nutrition-specific interventions we consider, school-baseddeworming is low cost and effective. The interventions we reviewed in the agriculture sector areexpensive when compared to nutrition-specific interventions, although very little cost effectiveness data are available for the nutrition-sensitive interventions to make carefulcomparisons. These findings point to a powerful set of nutrition-specific interventions and acandidate list of nutrition-sensitive approaches that represent a highly cost-effective approach toreducing child malnutrition in Zambia.